2009
DOI: 10.3354/meps08353
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and natural sources of ambient noise in the ocean

Abstract: Ocean ambient noise results from both anthropogenic and natural sources. Different noise sources are dominant in each of 3 frequency bands: low (10 to 500 Hz), medium (500 Hz to 25 kHz) and high (> 25 kHz). The low-frequency band is dominated by anthropogenic sources: primarily, commercial shipping and, secondarily, seismic exploration. Shipping and seismic sources contribute to ambient noise across ocean basins, since low-frequency sound experiences little attenuation, allowing for long-range propagation. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
609
0
23

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 881 publications
(635 citation statements)
references
References 58 publications
3
609
0
23
Order By: Relevance
“…It is also generated by a variety of man-made sources, such as ships and sonars. 2,3 This background sound in the ocean is called ambient noise. 4,5 Underwater ambient noise has been an important area of study in underwater acoustics and acoustical oceanography.…”
Section: Introductionmentioning
confidence: 99%
“…It is also generated by a variety of man-made sources, such as ships and sonars. 2,3 This background sound in the ocean is called ambient noise. 4,5 Underwater ambient noise has been an important area of study in underwater acoustics and acoustical oceanography.…”
Section: Introductionmentioning
confidence: 99%
“…However, our knowledge about ambient noise, the sound field against which signals must be detected, is still incomplete. Given that ambient noise has been increasing over the decades mainly due to shipping, and by as much as 12 dB in some areas (Hildebrand, 2009), ambient noise is now considered a major component of the total noise received by individuals.…”
Section: Priority Mammal Biology Questionsmentioning
confidence: 99%
“…Therefore, it is a challenging task to detect and distinguish the weak acoustic signal in complex ocean ambient noise. It has been reported that, in the past five decades, the artificial low frequency shipping noise radiation has increased by 10-15 dB [5][6][7]. This has negative implications for mammalian marine wild life [8,9].…”
Section: Introductionmentioning
confidence: 99%